A core-shell structure bromine complex positive electrode material and a preparation method thereof
Patent Information
- Application Number
- CN202610956262.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
碳材料凭借高比表面积与良好导电性可实现对溴基物质的初步吸附固定,但物理吸附作用较弱,在长时间循环过程中无法有效抑制溴的溶解与穿梭
(1)本发明提供的核壳结构溴络合正极材料,通过四层梯度化结构设计,从活性物质负载、界面结合、电子传导、溴穿梭抑制到表面润湿性调控实现全方位优化,从根本上解决传统溴基正极材料存在的挥发流失、穿梭效应、导电性差、循环稳定性差等技术问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cathode material technology, and more specifically, to a core-shell structured bromine complex cathode material and its preparation method. Background Technology
[0002] Energy storage technology is a key support for the large-scale application of new energy sources. New battery systems with high energy density, long cycle life, and high safety have become a research focus in materials science and electrochemistry. Bromine-based cathode materials, with their advantages of high theoretical capacity, moderate redox potential, abundant natural resources, and low cost, have shown great application potential in energy storage systems such as aqueous secondary batteries, flow batteries, and lithium-bromine batteries, and are considered an important candidate cathode material system for next-generation high-performance energy storage devices. However, elemental bromine and its bromine complexes have a series of inherent defects during electrochemical charge-discharge processes, which seriously restrict the practical application and industrialization of bromine-based cathode materials.
[0003] Elemental bromine and its conventional bromine complexes exhibit high volatility and solubility, readily dissolving into the electrolyte during battery cycling. This triggers a severe bromine shuttle effect, causing negative electrode corrosion, accelerated self-discharge, and irreversible loss of active materials, ultimately leading to rapid capacity decay and a significantly shortened cycle life. Furthermore, bromine-based active materials inherently possess low electronic conductivity and slow electrode reaction kinetics, exhibiting significant polarization under high-current charge-discharge conditions, making it difficult to meet practical application requirements in terms of rate performance. In addition, traditional supported bromine-based cathode materials are prone to structural collapse, active material desorption, and interfacial contact failure during long-term cycling, further exacerbating the degradation of electrochemical performance.
[0004] To address these issues, existing technologies often employ porous carbon materials, conductive polymers, and metal oxides as supports for the physical loading or chemical modification of bromine complexes. Carbon materials, with their high specific surface area and good conductivity, can achieve initial adsorption and fixation of bromine-based substances; however, their physical adsorption is weak and cannot effectively inhibit the dissolution and shuttle of bromine during long-term cycling. While conductive polymers possess certain structural coating and conductivity capabilities, single polymer coating layers typically have a loose structure, poor mechanical stability, and insufficient interfacial bonding with the core material, making it difficult to form a dense and effective barrier layer. Furthermore, their ability to target and anchor bromine complexes is limited.
[0005] Most current modification strategies focus only on optimizing a single performance aspect, lacking a systematic design encompassing molecular structure, interfacial bonding, and macroscopic morphology. This makes it difficult to simultaneously achieve multiple objectives, such as efficient and stable loading of active materials, rapid electron / ion transport, long-term suppression of the bromine shuttle effect, and optimization of electrode interface compatibility. Furthermore, the uncontrollable surface wettability of existing materials and their poor compatibility with different electrolyte systems further limit the improvement of overall battery performance.
[0006] Based on this, a novel core-shell structured bromine complex cathode material with stable structure, excellent conductivity, ability to precisely bind bromine active materials, and strong adaptability is provided, which is of great significance for promoting the practical development of bromine-based energy storage batteries. Summary of the Invention
[0007] In view of this, the present invention proposes a core-shell structured bromine complex cathode material and its preparation method, aiming to solve at least one of the problems in the current background technology.
[0008] This invention proposes a core-shell structured bromine complex cathode material, which includes: an active core, an intermediate transition layer, a main shell layer, and a functionalized modification layer; The active core is a composite core material of cyclodextrin-functionalized carbon nanotubes supported on bromine complex active materials; the intermediate transition layer is a primary layer of conductive polymer containing cyclodextrin. The main shell is a dense layer of conductive polymer containing cyclodextrin; The functionalized modification layer is a hydrophilic or hydrophobic adjustment layer, composed of ionic surfactants or fluoropolymers.
[0009] Preferably, the bromine complexing active material is one or more of quaternary ammonium polybrominates, imidazole bromine complexes, or pyridine bromine complexes; the cyclodextrin is α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, or methyl-β-cyclodextrin.
[0010] Preferably, the method for preparing the cyclodextrin-functionalized carbon nanotubes is as follows: Carbon nanotubes were subjected to ultrasonic oxidation treatment with a nitric acid-sulfuric acid mixed solution, and then mixed with cyclodextrin to carry out an epichlorohydrin crosslinking reaction to obtain the cyclodextrin-functionalized carbon nanotubes. In the nitric acid-sulfuric acid mixed solution, the volume ratio of nitric acid to sulfuric acid is 1:3; The mass ratio of cyclodextrin to carbon nanotubes is 1:0.5-5; The parameters for the ultrasonic oxidation treatment are: temperature 50-80℃, ultrasonic power 200-500W, and time 2-6 hours. The epichlorohydrin crosslinking reaction specifically involves adding epichlorohydrin at 60-80°C and reacting for 4-12 hours.
[0011] Preferably, the conductive polymer is polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene) or a copolymer thereof.
[0012] Preferably, the thickness of the intermediate transition layer is 5-30 nm, the thickness of the main shell layer is 50-200 nm, and the thickness of the functionalized modification layer is 2-10 nm.
[0013] This invention also provides a method for preparing the core-shell structured bromine complex cathode material described above, comprising the following steps: (1) Preparation of cyclodextrin-functionalized carbon nanotubes: cyclodextrin-functionalized carbon nanotubes are mixed with bromine complexes to obtain an active core; (2) The active core is dispersed in a first reaction solution containing conductive polymer monomers, cyclodextrin and weak oxidant, and a first in-situ polymerization is carried out to form an intermediate transition layer on the surface of the active core, thereby obtaining bilayer composite particles. (3) The bilayer composite particles are transferred to a second reaction solution containing conductive polymer monomers, cyclodextrin and strong oxidant to carry out a second in-situ polymerization to form a main shell layer. At the same time, cyclodextrin is embedded in the shell layer to obtain a three-layer composite particle. (4) The three-layer composite particles are immersed in a third reaction solution containing ionic surfactants or fluoropolymers to form the outermost functionalized modification layer. Finally, they are washed and dried to obtain the multi-layer core-shell structure bromine complex cathode material.
[0014] Preferably, the mass ratio of the cyclodextrin-functionalized carbon nanotubes to the bromine complex is 1:2-10. The mixing in step (1) specifically involves placing the cyclodextrin-functionalized carbon nanotubes and the bromine complex in a polar organic solvent and ultrasonically dispersing them for 30-90 minutes at a temperature of 20-40℃.
[0015] Preferably, the weak oxidant in step (2) is one or more of ammonium persulfate, ferric chloride, or iodine. The concentrations of the conductive polymer monomer, cyclodextrin, and weak oxidant in the first reaction solution are: 0.01-0.1 mol / L for conductive polymer monomer, 0.5-5 g / L for cyclodextrin, and 0.005-0.05 mol / L for weak oxidant. The parameters for the first in-situ polymerization are: reaction temperature of 0-5℃ and reaction time of 1-4 hours.
[0016] Preferably, the strong oxidant is one or more of ammonium persulfate, hydrogen peroxide, potassium permanganate or potassium dichromate. In step (2), the concentrations of the conductive polymer monomer, cyclodextrin and strong oxidant in the second reaction solution are: 0.1-0.5 mol / L for conductive polymer monomer, 1-6 g / L for cyclodextrin and 0.05-0.2 mol / L for strong oxidant. The parameters for the second in-situ polymerization are: reaction temperature of 20-40℃ and reaction time of 6-24 hours.
[0017] Preferably, the concentration of the ionic surfactant or fluoropolymer in the third reaction solution is 0.1-10 g / L.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The core-shell structured bromine complex cathode material provided by the present invention achieves comprehensive optimization from active material loading, interface bonding, electronic conduction, bromine shuttle inhibition to surface wettability regulation through a four-layer gradient structure design, fundamentally solving the technical problems of volatilization loss, shuttle effect, poor conductivity and poor cycle stability of traditional bromine-based cathode materials.
[0019] (2) The present invention uses cyclodextrin-functionalized carbon nanotubes as active core carriers. The high conductivity network and high specific surface area of carbon nanotubes provide a fast electron transport channel. At the same time, with the help of the unique host-guest inclusion effect and chemical cross-linking structure of cyclodextrin, the active substances of bromine complex are strongly chemically anchored and physically confined, which significantly reduces the dissolution, diffusion and volatilization of active substances and improves the utilization rate and structural stability of active substances.
[0020] (3) The present invention constructs a conductive polymer intermediate transition layer and a main shell containing cyclodextrin through stepwise in-situ polymerization. The thin transition layer can effectively improve the interfacial compatibility between the core and the shell, reduce the interfacial contact impedance, and enhance the structural bonding strength. The dense main shell not only constructs a continuous and interconnected three-dimensional conductive network, which greatly improves the overall electronic conductivity of the material, but also forms a strong physical barrier to suppress the bromine shuttle effect for a long time and reduce self-discharge and side reactions.
[0021] (4) This invention embeds cyclodextrin in situ into the conductive polymer shell, which can further optimize the stacking mode of the polymer chains, improve the shell density and mechanical stability, avoid swelling, cracking and shedding during long-term cycling, and at the same time provide additional binding sites for bromine complexes, enhancing the fixation effect on active materials. The outermost functionalized modification layer can precisely control the hydrophilicity and hydrophobicity of the material surface according to the electrolyte system, improve the interfacial wettability between the electrode and the electrolyte, accelerate ion transport and electrode reaction kinetics, and improve the rate performance of the battery.
[0022] (5) The cathode material prepared by this invention has high specific capacity, excellent rate performance and ultra-long cycle life. The preparation process is controllable and has good repeatability. It is suitable for various electrochemical energy storage systems such as aqueous energy storage batteries, flow batteries and lithium-bromine batteries, effectively improving the overall safety and stability of the battery. It has important scientific research value and broad industrial application prospects. Detailed Implementation
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0024] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0028] This invention provides a core-shell structured bromine complex cathode material, which includes: an active core, an intermediate transition layer, a main shell layer, and a functionalized modification layer; The active core is a composite core material of cyclodextrin-functionalized carbon nanotubes supported on bromine complex active materials; the intermediate transition layer is a primary layer of conductive polymer containing cyclodextrin. The main shell is a dense layer of conductive polymer containing cyclodextrin; The functionalized modification layer is a hydrophilic or hydrophobic adjustment layer, composed of ionic surfactants or fluoropolymers.
[0029] In this invention, the bromine complexing active material is preferably one or more of quaternary ammonium polybrominates, imidazole bromine complexes, or pyridine bromine complexes; the cyclodextrin is preferably α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, or methyl-β-cyclodextrin.
[0030] In this invention, the preferred method for preparing the cyclodextrin-functionalized carbon nanotubes is as follows: Carbon nanotubes were subjected to ultrasonic oxidation treatment with a nitric acid-sulfuric acid mixed solution, and then mixed with cyclodextrin to carry out an epichlorohydrin crosslinking reaction to obtain the cyclodextrin-functionalized carbon nanotubes. The preferred volume ratio of nitric acid to sulfuric acid in the nitric acid-sulfuric acid mixed solution is 1:3. The preferred mass ratio of cyclodextrin to carbon nanotubes is 1:0.5-5; The preferred parameters for the ultrasonic oxidation treatment are: temperature 50-80℃, ultrasonic power 200-500W, and time 2-6 hours; more preferably, temperature 60-70℃, ultrasonic power 300-400W, and time 3-4 hours.
[0031] The preferred method for the epichlorohydrin crosslinking reaction is to add epichlorohydrin at 60-80°C and allow the crosslinking reaction to proceed for 4-12 hours.
[0032] In this invention, the conductive polymer is preferably polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene) or copolymers thereof.
[0033] In this invention, the thickness of the intermediate transition layer is preferably 5-30 nm, the thickness of the main shell layer is preferably 50-200 nm, and the thickness of the functionalized modification layer is preferably 2-10 nm.
[0034] This invention also provides a method for preparing the core-shell structured bromine complex cathode material described above, comprising the following steps: (1) Preparation of cyclodextrin-functionalized carbon nanotubes: cyclodextrin-functionalized carbon nanotubes are mixed with bromine complexes to obtain an active core; Specifically, the preferred step is as follows: Nitric acid and sulfuric acid are mixed at a volume ratio of 1:3 to obtain a nitric acid-sulfuric acid mixed solution. Carbon nanotubes are placed in this mixed solution and subjected to ultrasonic oxidation treatment for 2–6 hours at a temperature of 50-80℃ and an ultrasonic power of 200-500W. After treatment, the solution is cooled to room temperature, centrifuged, repeatedly washed until neutral, and then dried to obtain surface-oxidized carbon nanotubes. Then, cyclodextrin is added to deionized water at a mass ratio of 1:0.5-5 and dispersed evenly. Epichlorohydrin is added, and a crosslinking reaction is carried out at 60-80℃ for 4-12 hours. After the reaction, the solution is centrifuged, washed, and vacuum dried to obtain cyclodextrin-functionalized carbon nanotubes. The raw materials were weighed according to a mass ratio of cyclodextrin-functionalized carbon nanotubes to bromine complex of 1:2-10. The two were placed together in a polar organic solvent, such as ethanol, methanol, acetonitrile, N,N-dimethylformamide or a mixture thereof, and ultrasonically dispersed at a temperature of 20-40℃ for 30-90 minutes to fully load the bromine complex active material onto the surface of the cyclodextrin-functionalized carbon nanotubes. After loading was completed, solid-liquid separation was performed to obtain the active core of the cyclodextrin-functionalized carbon nanotubes loaded with bromine complex active material.
[0035] This invention uses carbon nanotubes as the core carrier, providing a high specific surface area and a continuous conductive network for rapid electron transport, while also offering efficient loading sites for bromine-containing complexes. Ultrasonic oxidation of the carbon nanotubes using a nitric acid-sulfuric acid mixture introduces polar functional groups such as carboxyl and hydroxyl groups onto the nanotube surface, enhancing its dispersibility and reactivity, and providing binding sites for subsequent cyclodextrin crosslinking. Cyclodextrin is crosslinked to the carbon nanotube surface via epichlorohydrin, utilizing its unique cavity structure and host-guest inclusion effect to form a strong chemical anchoring and physical confinement of the bromine complex, significantly inhibiting the dissolution, diffusion, and volatilization of the bromine-containing active material, thereby improving the utilization rate and structural stability of the active material.
[0036] Furthermore, this invention involves ultrasonically combining cyclodextrin-functionalized carbon nanotubes with bromine complexes in a polar organic solvent. This allows the bromine-complexed active material to be uniformly loaded onto the carrier surface and within the pores, forming a highly active and stable core. This core possesses both high conductivity and strong bromine binding capacity, ensuring rapid electron conduction while reducing the bromine shuttle effect at its source, thus providing stable capacity output for the electrode.
[0037] (2) The active core is dispersed in a first reaction solution containing conductive polymer monomers, cyclodextrin and weak oxidant, and a first in-situ polymerization is carried out to form an intermediate transition layer on the surface of the active core, thereby obtaining bilayer composite particles. Specifically, this step is preferably as follows: the above-mentioned active core is uniformly dispersed in a first reaction solution, which contains a conductive polymer monomer, cyclodextrin, and a weak oxidant, wherein the concentration of the conductive polymer monomer is 0.01-0.1 mol / L, the concentration of the cyclodextrin is 0.5-5 g / L, and the concentration of the weak oxidant is 0.005-0.05 mol / L. A first in-situ polymerization reaction is carried out at a low temperature of 0-5℃ for 1-4 hours, forming a 5-30 nm thick cyclodextrin-containing conductive polymer primary intermediate transition layer on the surface of the active core. After the reaction is completed, the particles are centrifuged and washed to obtain bilayer composite particles with an active core and an intermediate transition layer.
[0038] The first reaction solution of this invention uses a weak oxidant, a low concentration of monomer, and low-temperature polymerization conditions to generate a thin and uniform conductive polymer nascent layer in situ on the surface of the active core. The intermediate transition layer can effectively improve the interfacial compatibility between the core and the main shell, reduce the interfacial contact impedance, enhance the bonding strength between the core and the outer structure, avoid problems such as uneven coating and delamination during subsequent polymerization, and simultaneously initially construct a conductive pathway to improve the electrode kinetic performance.
[0039] (3) The bilayer composite particles are transferred to a second reaction solution containing conductive polymer monomers, cyclodextrin and strong oxidant to carry out a second in-situ polymerization to form a main shell layer. At the same time, cyclodextrin is embedded in the shell layer to obtain a three-layer composite particle. Specifically, this step is preferably as follows: the bilayer composite particles are transferred to a second reaction solution containing conductive polymer monomers, cyclodextrin, and a strong oxidant, wherein the concentration of the conductive polymer monomers is 0.1-0.5 mol / L, the concentration of the cyclodextrin is 1-6 g / L, and the concentration of the strong oxidant is 0.05-0.2 mol / L. A second in-situ polymerization reaction is carried out at a temperature of 20-40℃ for 6-24 hours, forming a dense host shell layer containing cyclodextrin and conductive polymer with a thickness of 50-200 nm on the surface of the bilayer composite particles. Simultaneously, the cyclodextrin is in-situ embedded into the host shell layer. After the reaction is completed, the particles are centrifuged and washed to obtain three-layer composite particles.
[0040] The second reaction solution of this invention uses a strong oxidant and a high concentration of monomers to form a dense, continuous conductive polymer shell on the outside of the transition layer. This shell can further construct a three-dimensional interconnected conductive network, significantly improving the overall electronic conductivity of the material and reducing electrode polarization; at the same time, it acts as a robust physical barrier, effectively suppressing the bromine shuttle effect and reducing self-discharge and side reactions. In-situ embedding of cyclodextrins into the shell optimizes the polymer chain stacking structure, improves the shell density and mechanical stability, inhibits swelling and cracking during long-term cycling, and provides additional bromine complexation sites, enhancing the fixation effect of active substances.
[0041] (4) The three-layer composite particles are immersed in a third reaction solution containing ionic surfactants or fluoropolymers to form the outermost functionalized modification layer. Finally, they are washed and dried to obtain the multi-layer core-shell structure bromine complex cathode material.
[0042] Specifically, this step is preferably as follows: the three-layer composite particles are immersed in a third reaction solution, wherein the concentration of the ionic surfactant or fluoropolymer in the third reaction solution is 0.1-10 g / L. Through thorough immersion and coating, a hydrophilic or hydrophobic functionalized modification layer with a thickness of 2-10 nm is formed on the surface of the three-layer composite particles. Subsequently, unreacted impurities and excess reagents are thoroughly washed away with a solvent, and after vacuum drying, a four-layer core-shell structured bromine complex cathode material is finally obtained.
[0043] The outermost layer of this invention is surface-modified with ionic surfactants or fluoropolymers, which allows for precise control of the hydrophilic / hydrophobic balance of the material surface, improving the interfacial wettability between the electrode and the electrolyte, accelerating ion transport and interfacial charge transfer, and optimizing battery rate performance. The flexible selection of hydrophilic or hydrophobic modifications based on the electrolyte system can improve the material's adaptability to different energy storage systems and broaden its application range.
[0044] In the above steps, the solvents for the first reaction solution, the second reaction solution, and the third reaction solution are all deionized water.
[0045] This invention achieves integrated functions such as high-efficiency loading, interface optimization, enhanced conductivity, bromine shuttle suppression, and wettability regulation through a gradient design of an active core, intermediate transition layer, main shell, and functional modification layer. It fundamentally solves the problems of high volatility, significant shuttle effect, poor conductivity, and poor cycle stability of traditional bromine-based cathode materials, enabling the cathode material to have both high specific capacity, excellent rate performance, and ultra-long cycle life. It is suitable for various electrochemical energy storage systems such as aqueous batteries, flow batteries, and lithium-bromine batteries.
[0046] Example 1 (1) Preparation of cyclodextrin-functionalized carbon nanotubes Nitric acid and sulfuric acid were mixed evenly at a volume ratio of 1:3 to obtain a mixed solution. Carbon nanotubes were added to the mixed solution and fully impregnated. The solution was then placed in an ultrasonic reactor and subjected to ultrasonic oxidation treatment at 50°C and 200W for 2 hours. After the reaction was completed, the solution was cooled to room temperature. The solid product was separated by centrifugation and repeatedly washed with deionized water until the washing solution was neutral. The solid was then placed in a vacuum drying oven at 60°C and dried for 12 hours to obtain surface-oxidized carbon nanotubes.
[0047] β-Cyclodextrin and carbon nanotubes were added to acetonitrile at a mass ratio of 1:2 and mechanically stirred for 30 minutes until uniformly dispersed. Epichlorohydrin was added, and the mixture was stirred and crosslinked for 8 hours under a water bath at 70°C. After the reaction was completed, the mixture was centrifuged, washed three times with deionized water, and dried under vacuum at 60°C to constant weight to obtain β-cyclodextrin-functionalized carbon nanotubes.
[0048] (2) Preparation of active core Weigh the materials according to the ratio of β-cyclodextrin-functionalized carbon nanotubes to tetrabutylammonium bromide polybromin at 1:5 (mass ratio), add them together to deionized water, and ultrasonically disperse at 20°C for 90 minutes to fully load the bromine complex active substance onto the surface and pores of the functionalized carbon nanotubes. After dispersion, centrifuge to remove the supernatant to obtain the active core of the cyclodextrin-functionalized carbon nanotubes loaded with bromine complex. Proceed directly to the next step without drying.
[0049] (3) In-situ polymerization of intermediate transition layer The active core was dispersed in a first reaction solution prepared with deionized water, wherein the concentration of pyrrole monomer was 0.01 mol / L, the concentration of β-cyclodextrin was 0.5 g / L, and the concentration of ammonium persulfate was 0.05 mol / L. The mixture was stirred for 30 minutes to form a uniform suspension. The system was placed in a low-temperature ice-water bath at 2°C and stirred for 2 hours to carry out the first in-situ polymerization reaction. A primary transition layer containing cyclodextrin and polypyrrole with a thickness of about 15 nm was formed on the surface of the active core. After polymerization, the mixture was centrifuged and washed twice with deionized water to obtain bilayer composite particles.
[0050] (4) In-situ polymerization of the main shell The bilayer composite particles were transferred to a second reaction solution prepared with deionized water, wherein the concentration of pyrrole monomer was 0.1 mol / L, the concentration of β-cyclodextrin was 6 g / L, and the concentration of ammonium persulfate was 0.2 mol / L. The mixture was stirred for 30 minutes to disperse the particles evenly, and then carried out a second in-situ polymerization reaction at room temperature of 25°C for 12 hours. A dense host shell of cyclodextrin-containing polypyrrole with a thickness of about 100 nm was formed on the surface of the bilayer composite particles. After the reaction was completed, the particles were centrifuged and washed three times alternately with deionized water and ethanol to obtain a three-layer composite particle.
[0051] (5) Preparation of functionalized modification layer and finished product The three-layer composite particles were immersed in a third reaction solution prepared with deionized water, wherein the concentration of sodium dodecylbenzenesulfonate was 1 g / L. The mixture was stirred and immersed at room temperature for 30 minutes to uniformly coat the surface with a hydrophilic modification layer with a thickness of about 5 nm. Then, the particles were centrifuged, washed with deionized water to remove unadsorbed surfactants, and dried in a vacuum drying oven at 60 °C for 12 hours to finally obtain a four-layer core-shell structured bromine complex cathode material.
[0052] Example 2 (1) Preparation of cyclodextrin-functionalized carbon nanotubes Nitric acid and sulfuric acid were mixed evenly at a volume ratio of 1:3 to obtain a mixed solution. Carbon nanotubes were added to the mixed solution and fully immersed. The solution was then placed in an ultrasonic reactor and subjected to ultrasonic oxidation treatment at 50°C and 500W for 6 hours. After the reaction was completed, the solution was cooled to room temperature. The solid product was separated by centrifugation and repeatedly washed with deionized water until the washing solution was neutral. The solid was then placed in a vacuum drying oven at 60°C and dried for 12 hours to obtain surface-oxidized carbon nanotubes.
[0053] β-Cyclodextrin and carbon nanotubes were added to methanol at a mass ratio of 1:2 and mechanically stirred for 30 minutes until uniformly dispersed. Epichlorohydrin was added, and the mixture was stirred and crosslinked for 8 hours under a water bath at 70°C. After the reaction was completed, the mixture was centrifuged, washed three times with deionized water, and dried under vacuum at 60°C to constant weight to obtain β-cyclodextrin-functionalized carbon nanotubes.
[0054] (2) Preparation of active core Weigh the materials according to the ratio of β-cyclodextrin-functionalized carbon nanotubes to tetrabutylammonium bromide polybromin at 1:5 (mass ratio), add them together to deionized water, and ultrasonically disperse at 20°C for 90 minutes to fully load the bromine complex active substance onto the surface and pores of the functionalized carbon nanotubes. After dispersion, centrifuge to remove the supernatant to obtain the active core of the cyclodextrin-functionalized carbon nanotubes loaded with bromine complex. Proceed directly to the next step without drying.
[0055] (3) In-situ polymerization of intermediate transition layer The active core was dispersed in a first reaction solution prepared with deionized water, wherein the concentration of pyrrole monomer was 0.1 mol / L, the concentration of β-cyclodextrin was 0.5 g / L, and the concentration of ammonium persulfate was 0.05 mol / L. The mixture was stirred for 30 minutes to form a uniform suspension. The system was placed in a low-temperature ice-water bath at 2°C and stirred for 2 hours to carry out the first in-situ polymerization reaction. A primary transition layer containing cyclodextrin and polypyrrole with a thickness of about 15 nm was formed on the surface of the active core. After polymerization, the mixture was centrifuged and washed twice with deionized water to obtain bilayer composite particles.
[0056] (4) In-situ polymerization of the main shell The bilayer composite particles were transferred to a second reaction solution prepared with deionized water, wherein the concentration of pyrrole monomer was 0.5 mol / L, the concentration of β-cyclodextrin was 6 g / L, and the concentration of ammonium persulfate was 0.05 mol / L. The mixture was stirred for 30 minutes to disperse the particles evenly, and then carried out a second in-situ polymerization reaction at room temperature of 25°C for 12 hours. A dense host shell of cyclodextrin-containing polypyrrole with a thickness of about 100 nm was formed on the surface of the bilayer composite particles. After the reaction was completed, the particles were centrifuged and washed three times alternately with deionized water and ethanol to obtain a three-layer composite particle.
[0057] (5) Preparation of functionalized modification layer and finished product The three-layer composite particles were immersed in a third reaction solution prepared with deionized water, wherein the concentration of sodium dodecylbenzenesulfonate was 10 g / L. The mixture was stirred and immersed at room temperature for 30 minutes to uniformly coat the surface with a hydrophilic modification layer with a thickness of about 5 nm. Then, the particles were centrifuged, washed with deionized water to remove unadsorbed surfactants, and dried in a vacuum drying oven at 60 °C for 12 hours to finally obtain a four-layer core-shell structured bromine complex cathode material.
[0058] Comparative Example 1 (1) Take unfunctionalized and unoxidized raw carbon nanotubes without cyclodextrin crosslinking modification. (2) The original carbon nanotubes and tetrabutylammonium bromide polybromin were added to acetonitrile solvent at a mass ratio of 1:5 and ultrasonically dispersed at 30°C for 60 minutes to load the bromine complex through physical adsorption only.
[0059] (3) After dispersion, centrifuge directly and vacuum dry at 60°C for 12 hours to obtain a conventional bromine-based cathode material without core-shell structure, cyclodextrin, conductive polymer coating, or surface modification.
[0060] Performance testing The following tests were performed on Examples 1-2 and Comparative Example 1. I. Test Indicators (1) Initial discharge specific capacity and rate discharge specific capacity The discharge performance test method for lithium-ion battery cathode materials was performed according to GB / T 36276-2018. The cathode material, acetylene black, and PVDF were mixed in a mass ratio of 85:10:5 to form a slurry, which was then coated onto titanium foil and assembled into CR2032 coin cells. The specific capacity was recorded during constant current discharge at 0.1C and 5C rates.
[0061] (2) Cyclic stability and capacity retention The test was conducted according to GB / T 36653-2018, "Test Method for Cyclic Performance of Cathode Materials for Lithium-ion Batteries." The battery underwent 1000 constant-current charge-discharge cycles at a 1C rate, and the capacity retention was calculated.
[0062] (3) Average Coulomb efficiency Data is collected synchronously by the charge / discharge test system and calculated as: discharge capacity / charge capacity × 100%.
[0063] (4) 72h self-discharge rate After the battery is fully charged and left to stand for 72 hours, the result is calculated as (initial capacity - capacity after standing) / initial capacity × 100%.
[0064] (5) Charge transfer resistance (Rct) EIS was tested using an electrochemical workstation, with a frequency range of 10⁻²*10⁻². 5 The charge transfer resistance was obtained by fitting the Hz.
[0065] (6) Bromine ion exudation After 100 cycles at 1C, the electrolyte was collected, and the bromide ion concentration was determined by ion chromatography.
[0066] II. Test Results The test results are shown in Table 1. Table 1 Test Results As shown in Table 1, the core-shell structured bromine complex cathode materials prepared in Examples 1 and 2 of this invention have significantly higher first-discharge specific capacity and high-rate discharge specific capacity than the comparative examples, and the utilization rate of active materials and electron / ion transport efficiency are significantly improved.
[0067] In Examples 1 and 2, the capacity retention rate exceeded 85% after 1000 cycles at 1C, and the coulombic efficiency remained stable at over 98.5%, demonstrating a cycle stability far superior to that of the comparative cathode materials with traditional structures.
[0068] The self-discharge rates of Examples 1 and 2 after 72 hours were both less than 5%, and the amount of bromide ion leakage was much lower than that of the comparative example. This indicates that the core-shell structure and cyclodextrin functionalization design can effectively suppress the bromine shuttle effect and reduce the loss of active materials and negative electrode corrosion.
[0069] The charge transfer resistance (Rct) of Examples 1 and 2 is much smaller than that of the comparative example, the electrode interface impedance is lower, the reaction kinetics are faster, and the polarization is smaller under high current charge and discharge.
[0070] Based on the above, this invention solves the technical defects of traditional bromine-based cathode materials, such as poor conductivity, severe shuttle effect, and short cycle life, through the synergistic effect of four-layer core-shell structure, cyclodextrin functionalization, stepwise in-situ polymerization, and surface functional modification. Its electrochemical performance is comprehensively superior to that of conventional bromine-based cathode materials.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A core-shell structured bromine complex cathode material, characterized in that, The core-shell structured bromine complex cathode material comprises: an active core, an intermediate transition layer, a main shell layer, and a functionalized modification layer; The active core is a composite core material of cyclodextrin-functionalized carbon nanotubes supported on bromine complex active materials; the intermediate transition layer is a primary layer of conductive polymer containing cyclodextrin. The main shell is a dense layer of conductive polymer containing cyclodextrin; The functionalized modification layer is a hydrophilic or hydrophobic adjustment layer, composed of ionic surfactants or fluoropolymers.
2. The core-shell structured bromine complex cathode material according to claim 1, characterized in that, The bromine complexing active material is one or more of quaternary ammonium polybrominates, imidazole bromine complexes, or pyridine bromine complexes; the cyclodextrin is α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, hydroxypropyl-β-cyclodextrin, or methyl-β-cyclodextrin.
3. The core-shell structured bromine complex cathode material according to claim 1, characterized in that, The preparation method of the cyclodextrin-functionalized carbon nanotubes is as follows: Carbon nanotubes were subjected to ultrasonic oxidation treatment with a nitric acid-sulfuric acid mixed solution, and then mixed with cyclodextrin to carry out an epichlorohydrin crosslinking reaction to obtain the cyclodextrin-functionalized carbon nanotubes. In the nitric acid-sulfuric acid mixed solution, the volume ratio of nitric acid to sulfuric acid is 1:3; The mass ratio of cyclodextrin to carbon nanotubes is 1:0.5-5; The parameters for the ultrasonic oxidation treatment are: temperature 50-80℃, ultrasonic power 200-500W, and time 2-6 hours. The epichlorohydrin crosslinking reaction specifically involves adding epichlorohydrin at 60-80°C and reacting for 4-12 hours.
4. The core-shell structured bromine complex cathode material according to claim 1, characterized in that, The conductive polymer is polypyrrole, polyaniline, poly(3,4-ethylenedioxythiophene) or a copolymer thereof.
5. The core-shell structured bromine complex cathode material according to claim 1, characterized in that, The thickness of the intermediate transition layer is 5-30 nm, the thickness of the main shell layer is 50-200 nm, and the thickness of the functionalized modification layer is 2-10 nm.
6. A method for preparing a core-shell structured bromine complex cathode material according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Preparation of cyclodextrin-functionalized carbon nanotubes: cyclodextrin-functionalized carbon nanotubes are mixed with bromine complexes to obtain an active core; (2) The active core is dispersed in a first reaction solution containing conductive polymer monomers, cyclodextrin and weak oxidant, and a first in-situ polymerization is carried out to form an intermediate transition layer on the surface of the active core, thereby obtaining bilayer composite particles. (3) The bilayer composite particles are transferred to a second reaction solution containing conductive polymer monomers, cyclodextrin and strong oxidant to carry out a second in-situ polymerization to form a main shell layer. At the same time, cyclodextrin is embedded in the shell layer to obtain a three-layer composite particle. (4) The three-layer composite particles are immersed in a third reaction solution containing ionic surfactants or fluoropolymers to form the outermost functionalized modification layer. Finally, they are washed and dried to obtain the multi-layer core-shell structure bromine complex cathode material.
7. The method for preparing the core-shell structured bromine complex cathode material according to claim 6, characterized in that, The mass ratio of the cyclodextrin-functionalized carbon nanotubes to the bromine complex is 1:2-10. The mixing in step (1) specifically involves placing the cyclodextrin-functionalized carbon nanotubes and the bromine complex in a polar organic solvent and ultrasonically dispersing them for 30-90 minutes at a temperature of 20-40℃.
8. The method for preparing the core-shell structured bromine complex cathode material according to claim 6, characterized in that, The weak oxidant mentioned in step (2) is one or more of ammonium persulfate, ferric chloride or iodine. The concentrations of conductive polymer monomer, cyclodextrin and weak oxidant in the first reaction solution are: conductive polymer monomer 0.01-0.1 mol / L, cyclodextrin 0.5-5 g / L, weak oxidant 0.005-0.05 mol / L. The parameters of the first in-situ polymerization are: reaction temperature 0-5℃, reaction time 1-4 hours.
9. The method for preparing the core-shell structured bromine complex cathode material according to claim 6, characterized in that, The strong oxidant is one or more of ammonium persulfate, hydrogen peroxide, potassium permanganate or potassium dichromate. In step (2), the concentrations of conductive polymer monomer, cyclodextrin and strong oxidant in the second reaction solution are: conductive polymer monomer 0.1-0.5 mol / L, cyclodextrin 1-6 g / L and strong oxidant 0.05-0.2 mol / L. The parameters of the second in-situ polymerization are: reaction temperature 20-40℃ and reaction time 6-24 hours.
10. The method for preparing the core-shell structured bromine complex cathode material according to claim 6, characterized in that, The concentration of ionic surfactants or fluoropolymers in the third reaction solution is 0.1-10 g / L.
